Storage stability of chilled minimally processed shredded cabbage - Ibrahim, Roshita (2003)
Minimally processed products are a rapidly growing segment for retail market and food service horticultural industry as they match the consumers' demand for product freshness and convenience. The shelf-life extension of these fresh-cut products is therefore relevant because of its economic impact. Packaging can be one of the important factors in determining the storage stability and quality of these freshcut products. The shelf life of minimally processed fruits and vegetables is often limited by enzymatic browning. The organoleptic properties of fruits and vegetables are strongly altered by the appearance of brown pigments. This study was conducted to determine the effects of using different types of polymeric films (Polypropylene (PP), Low Density Polyethylene (LDPE), High Density Polyethylene (HDPE) and PVC cling wrap (Control» of varying permeabilities to gases and water vapour and also with and without the application of vacuum packaging on the physico-chemical, biochemical, microbiological characteristics and sensory aspects of the minimally processed (MP) shredded cabbage during storage at 5±loC; 90-95% RH. A study was also conducted on the effects of dipping into 4 different anti-browning solutions namely 1% ascorbic acid, 0.1% sodium metabisulphite, 0.5% L-cysteine + 0.1% citric acid and 0.1% acetic acid on the storage stability of shredded cabbage. Sample dipped in distilled water was used as a control. Physico-chemical characteristics were determined by quantitative measurements of weight loss, colour, texture, ascorbic acid content, pH, titratable acidity, total soluble solid, chlorophyll content, polyphenol oxidase (PPO) activity and degree of browning. Carbon dioxide and ethylene production in the package atmosphere during storage were also determined with gas chromatography. The microbial characteristics determined were mesophilic and psychrotrophic bacterial counts and mold and yeast counts. Sensory evaluation involved subjective acceptability and descriptive analyses. Data collected were analyzed using ANOVA and Duncan Multiple Range Test (DMRT) at 5% significant level. Generally, in almost all the analyses done, the quality of the MP shredded cabbage deteriorated with increase in storage time. Among all the packaging films used, it was found that PP which is the least permeable film for gases and water vapour, could extend the shelf life of the MP shredded cabbage almost up to 3 weeks with minimum colour change, reduction in ascorbic acid content and deterioration in sensory properties, and marginally low changes in other parameters tested. Whilst PVC cling wrap (control) was found to be the least effective packaging film. Different packaging systems did not affect the microflora of the shredded cabbage which was predominantly bacteria, small numbers of yeasts and only an occasional mold for both mesophilic and psychrotrophic microorganisms. Samples packed in vacuum packaging showed no significance difference with those in non-vacuum packaging in almost all the parameters tested for all the different packaging films, even though the air from the package headspace which can cause oxidation spoilage to the produce had been removed. Anti-browning treatment of 0.1% sodium metabisulphite gave the best sensory properties and visual colour retention followed by 0.1% acetic acid solution. Mean while 0.5% L-cysteine + 0.1% citric acid and 1% ascorbic acid solutions were found to be not very good anti-browning agents for the MP shredded cabbage as they gave worse results compared to control.